Exponents of Negative Numbers

πŸ†Practice powers of negative numbers

Exponentiation of Negative Numbers

Negative number raised to an even power

Raising any negative number to an even power will result in a positive outcome.
When nn is even:
(βˆ’x)n=xn(-x)^n=x^n

Negative number raised to an odd power

Raising any negative number to an odd power will result in a negative outcome.
When nn is odd:
(βˆ’x)n=βˆ’(x)n(-x)^n=-(x)^n

What is the difference between a power that is inside parentheses and one that is outside of them?

When the exponent is outside the parentheses - it applies to everything inside them.
When the exponent is inside the parentheses - it applies only to its base and not to the minus sign that precedes it.

Start practice

Test yourself on powers of negative numbers!

einstein

\( 9= \)

Practice more now

Exponentiation of Negative Numbers

In this article, you will learn everything you need to know about the exponentiation of negative numbers and understand the difference between a power that is inside the parentheses and another that appears outside of them.
Shall we start?


Laws of Exponents in Negative Numbers

So far, we have learned to solve powers of positive numbers always obtaining positive results.
When a negative number is raised to a certain power, the result can be either positive or negative.


Join Over 30,000 Students Excelling in Math!
Endless Practice, Expert Guidance - Elevate Your Math Skills Today
Test your knowledge

Negative number raised to an even power

Raising any negative number to an exponent that is an even number, even power, will result in a positive outcome.

For example

(βˆ’3)2=(-3)^2=
If we want to simplify the exercise we will get: (βˆ’3)Γ—(βˆ’3)=(-3) \times (-3)=
Negative times negative = Positive
Therefore, the result will be 99.
When the base is a negative number and the exponent is even, we can ignore the minus sign. Let's formulate it like this:
When nnΒ is even:
(βˆ’x)n=xn(-x)^n=x^n


Negative number raised to an odd power

When raising any negative number to an exponent that is an odd number, odd power, the result will be negative.

For example

(βˆ’3)3=(-3)^3=
If we want to simplify the exercise we will get: (βˆ’3)Γ—(βˆ’3)Γ—(βˆ’3)=(-3) \times (-3) \times (-3)=
Negative times negative = Positive
Positive times negative = Negative
Therefore, the result will be βˆ’27-27.
When the base is a negative number and the exponent is odd, we cannot ignore the minus sign, the result will always be negative.
Let's formulate it as a rule:
When nn is odd:

(βˆ’x)n=βˆ’(x)n(-x)^n=-(x)^n

Do you know what the answer is?

Let's Practice

Solve the exercise

(βˆ’4)3=(-4)^3=

Solution:
In this exercise, the exponent is odd.
Therefore, the result must necessarily be negative.
We will obtain:
(βˆ’4)Γ—(βˆ’4)Γ—(βˆ’4)=βˆ’64(-4) \times (-4) \times (-4)=-64


Solve the exercise

(βˆ’2)4=(-2)^4=

Solution:
In this exercise, the exponent is even. Consequently, we can ignore the minus sign and the result will be positive.
We will obtain:
(βˆ’2)Γ—(βˆ’2)Γ—(βˆ’2)Γ—(βˆ’2)=16(-2) \times (-2) \times (-2) \times (-2)=16


Check your understanding

Solve the exercise

(βˆ’5)5=(-5)^5=

Solution:
In this exercise, the exponent is odd. Consequently, the result will be negative.
We will obtain:
(βˆ’5)Γ—(βˆ’5)Γ—(βˆ’5)Γ—(βˆ’5)Γ—(βˆ’5)=βˆ’3125(-5) \times (-5) \times (-5) \times (-5) \times (-5)=-3125


What is the difference between a power that is inside parentheses and one that is outside of them?

It is important that you know that the difference is very large.

When the exponent appears outside of the parentheses
We multiply the number inside the parentheses by itself, as many times as indicated by the number representing the exponent.
For example:
(βˆ’4)2=(-4)^2=
(βˆ’4)Γ—(βˆ’4)=16(-4) \times (-4)=16

On the other hand, when the exponent is inside the parentheses (sometimes, without any parentheses)
Thus:
(βˆ’42)=(-4^2 )=
or
βˆ’(42)=-(4^2 )=
or
βˆ’42=-4^2=
The exponent applies only and exclusively to the base number and not to the minus sign that precedes it.
Therefore, we will calculate the power and add the minus as an annex.
We will obtain:
βˆ’42=βˆ’16-4^2=-16

We have obtained 22 different answers! That's why it is necessary to pay close attention to understand well to which part of the exercise the power applies.
If the exponent is outside the parentheses - it applies to everything inside them.
If the exponent is inside the parentheses - it applies only to its base and not to the minus sign that precedes it.

Let's see how this is done in slightly more complicated exercises:

Do you think you will be able to solve it?

Solve the exercise

(βˆ’2)4βˆ’32=(-2)^4-3^2=

Solution:
Let's start with (βˆ’2)4(-2)^4
The positive exponent is outside the parentheses, therefore, it applies to the entire βˆ’2-2.
We will obtain: (βˆ’2)4=16(-2)^4 = 16
Let's rewrite the exercise, we will get:
16βˆ’32=16-3^2=
Now let's continue with the other part of the exercise.
In the second monomial, there are no parentheses, meaning the exponent applies only to the 33 without taking into account the minus sign that precedes it.
We know that
32=93^2= 9
Therefore, let's rewrite the exercise in the following way:
16βˆ’9=716-9=7
Note –> Although it's true that the power is positive, it does not apply to the entire βˆ’3-3 therefore, we will not write 99 but,βˆ’9-9.


Examples and exercises with solutions on Exponentiation of negative numbers

Exercise #1

9= 9=

Video Solution

Step-by-Step Solution

To solve this problem, we need to evaluate expressions by applying the rules of exponents and the effects of parentheses on negative numbers:

  • (βˆ’3)2(-3)^2: When a negative number is squared, the result is positive. So, (βˆ’3)2(-3)^2 means βˆ’3Γ—βˆ’3=9-3 \times -3 = 9.
  • βˆ’(βˆ’3)2-(-3)^2: This means βˆ’1Γ—(βˆ’3Γ—βˆ’3)-1 \times (-3 \times -3) because squaring a number negates the negative sign inside parentheses, resulting in βˆ’9-9.
  • βˆ’(3)2-(3)^2: This equals βˆ’1Γ—(3Γ—3)=βˆ’9-1 \times (3 \times 3) = -9, as the negative sign is outside the squared value.
  • βˆ’3-3: This is simply βˆ’3-3.

Only (βˆ’3)2(-3)^2 equals 9, confirming it as the correct expression required by the problem.

Therefore, the solution to the problem is (βˆ’3)2 (-3)^2 .

Answer

(βˆ’3)2 (-3)^2

Exercise #2

Solve the following expression:

(βˆ’8)2= (-8)^2=

Video Solution

Step-by-Step Solution

When we have a negative number raised to a power, the location of the minus sign is very important.

If the minus sign is inside or outside the parentheses, the result of the exercise can be completely different.

 

When the minus sign is inside the parentheses, our exercise will look like this:

(-8)*(-8)=

Since we know that minus times minus is actually plus, the result will be positive:

(-8)*(-8)=64

 

Answer

64 64

Exercise #3

βˆ’(2)2= -(2)^2=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Calculate (2)2 (2)^2
  • Step 2: Apply the negative sign

Now, let's work through each step:
Step 1: Calculate (2)2 (2)^2 . This is equal to 2Γ—2=4 2 \times 2 = 4 .
Step 2: Apply the negative sign: The expression βˆ’(2)2-(2)^2 now becomes βˆ’4-4.

Therefore, the value of the expression βˆ’(2)2-(2)^2 is βˆ’4 -4 .

This matches choice 4, which is βˆ’4 -4 .

Answer

βˆ’4 -4

Exercise #4

(βˆ’2)7= (-2)^7=

Video Solution

Step-by-Step Solution

To solve for (βˆ’2)7(-2)^7, follow these steps:

  • Step 1: Identify the base and the exponent given in the expression, which are βˆ’2-2 and 77, respectively.
  • Step 2: Recognize that since the exponent is 77, which is an odd number, the result of the power will remain negative: (βˆ’2)7(-2)^7 will be βˆ’(27)- (2^7).
  • Step 3: Compute 272^7. This involves multiplying 22 by itself 77 times:
    2Γ—2=42 \times 2 = 4
    4Γ—2=84 \times 2 = 8
    8Γ—2=168 \times 2 = 16
    16Γ—2=3216 \times 2 = 32
    32Γ—2=6432 \times 2 = 64
    64Γ—2=12864 \times 2 = 128
    Thus, 27=1282^7 = 128.
  • Step 4: Apply the negative sign to the result of 272^7, resulting in βˆ’128-128.

Therefore, the value of (βˆ’2)7(-2)^7 is βˆ’128-128.

Answer

βˆ’128 -128

Exercise #5

36= 36=

Video Solution

Step-by-Step Solution

To determine which expression equals 36, we need to consider how squaring works with negative numbers:
Step 1: Consider the expression (βˆ’6)2(-6)^2. This means that we take -6 and multiply it by itself:
(βˆ’6)Γ—(βˆ’6)=36(-6) \times (-6) = 36

Step 2: Consider the expression βˆ’(6)2-(6)^2. Here, the square acts only on 6, not on the negative sign in front because of the absence of parentheses around -6:
βˆ’(6Γ—6)=βˆ’36-(6 \times 6) = -36

Therefore, the expression (βˆ’6)2(-6)^2 correctly equals 36.

The correct choice that satisfies 36= 36 = is (βˆ’6)2(-6)^2.

Answer

(βˆ’6)2 (-6)^2

Test your knowledge
Start practice